DENTAL SERVICES – TO FEAR OR NOT TO FEAR? THE EFFECT OF MUSIC ON PAIN PERCEPTIONS - Ancuța REMETE; Laura BACALI; Marcel Ciprian POP; Brîndușa Mariana BEJAN; Monica BOGDAN; Andrei PICOȘ (Management & Marketing)
In the tertiary sector of economy, consumers have been noticed to pay great attention to dental care services as they make use of such services quite frequently and are emotionally involved in the supply process to a great extent. Among adults, the dentist-patient relationship is often governed by stress, anxiety and fear. In this study, the authors propose exposing the patient to music as a component of ambience for a set amount of time, believing that this external factor may help to alleviate stress and rethink patients' opinions of dentists. To this end, the authors used the EPOCx electroencephalogram (EEG) and conducted the pilot experimental study, where the individuals in the sample were divided into four groups: a control group, on which no intervention was exerted (G1) and three experimental groups. Subjects in G2 were exposed to music without prior notice, study participants in G3 knew the experimental protocol, and those in G4 selected their own music. Using electroencephalogram signals, the authors monitored the reactions of patients in the experimental groups, which were then compared with the signals obtained for individuals in the G1 group. The results showed significant variations for subjects exposed to music, which were most evident in the right parietal cortex, which is responsible, among other things, for the emergence of positive emotions.